203 Feeding a calf starter containing monensin alone or in combination with a blend of essential oils and a proprietary cobalt source to Holstein calves. (30th November 2020) - Wu, Jianping; Guo, Jinsheng; Liu, Ting; Chen, Hao; Bai, Yan; Casper, David P
Abstract: Gut health is critical for neonatal calves, and nutritional technologies are needed for disease and stress prevention. Previous work feeding Monensin (MON) in combination with a blend of essential oils and a proprietary cobalt source (EOC) blend had demonstrated improved calf gut health and growth performance. The objective was to evaluate MON and EOC alone or in combination on calf growth performance. Eighty (80) new born Holstein calves were randomly assigned to one of four treatments arranged in a 2 x 2 factorial (MON and EOC). Treatments were: 1) Control without MON or EOC added to the calf starter (CS); 2) MON: 50.8 mg/kg CS (Norvikon Biotechnology Co., Hunan, China); 3) EOC: 44.1 mg/kg CS (Rum-A-Fresh, Ralco Inc. Marshall, MN); 4) MON+EOC: MON and EOC added to CS. Calves were fed colostrum followed by whole milk through weaning at 42 d, while CS was fed ad libitum through the 70-d experimental period. The MON by EOC interaction was found to be nonsignificant (P > 0.41) for growth performance. Calves fed without or with MON demonstrated similar (P > 0.70) body weight (BW; 68.7 and 68.9 kg without and with MON, respectively), while calves fed EOC demonstrated greater (P < 0.01) BW (67.3 and 70.4 kg without and with EOC, respectively) compared with calves fed without EOC. Calves fed a CS containing MON were similar (P > 0.47) in ADG (0.88 and 0.91 kg/d) compared with calves fed without MON; however, calves fed a CS with EOC increased (P < 0.01) ADG (0.84 and 0.95 kg/d) 13% through the 70 d experimental period compared with calves not fed EOC. These data demonstrate that EOC and MON fed in combination was not beneficial for enhancing growth performance, but that calf growth performance can be improved with EOC compared to MON.